2021
DOI: 10.1186/s12909-021-02920-4
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality-based neurological examination teaching tool(VRNET) versus standardized patient in teaching neurological examinations for the medical students: a randomized, single-blind study

Abstract: Background The conventional methods for teaching neurological examination with real patients to medical students have some limitations if the patient with the symptom or disease is not available. Therefore, we developed a Virtual Reality-based Neurological Examination Teaching Tool (VRNET) and evaluated its usefulness in in teaching neurological examinations for the medical students. Methods In this prospective, randomized, single-blind study, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 30 publications
2
12
0
5
Order By: Relevance
“…Despite the diversification of virtual simulators/platforms/systems used in undergraduate medical education, we found that 48 (52%) studies ( 18 , 22 , 23 , 27 31 , 33 35 , 37 39 , 42 , 44 48 , 50 , 52 , 54 , 57 67 , 71 , 72 , 75 , 78 , 81 84 , 93 , 96 , 99 , 101 , 103 , 105 ) reported the immersive VR application, which is characterized by the use of VR equipment consisting of head-mounted displays (headsets or goggles) and/or hand controllers. This finding suggested that VR might be a typical and popular representative of modern VS technology used in medical education.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…Despite the diversification of virtual simulators/platforms/systems used in undergraduate medical education, we found that 48 (52%) studies ( 18 , 22 , 23 , 27 31 , 33 35 , 37 39 , 42 , 44 48 , 50 , 52 , 54 , 57 67 , 71 , 72 , 75 , 78 , 81 84 , 93 , 96 , 99 , 101 , 103 , 105 ) reported the immersive VR application, which is characterized by the use of VR equipment consisting of head-mounted displays (headsets or goggles) and/or hand controllers. This finding suggested that VR might be a typical and popular representative of modern VS technology used in medical education.…”
Section: Resultsmentioning
confidence: 82%
“…From the 92 published studies, VS was reported to be applied in the educational practice involving undergraduate medical students across 25 countries including the United States [26 studies ( 15 40 )], the United Kingdom [9 studies ( 41 49 )], Germany [7 studies ( 50 – 56 )], China [6 studies ( 10 , 57 61 )], Denmark [6 studies ( 62 – 67 )], France [4 studies ( 68 71 )], Japan [4 studies ( 72 75 )], Sweden [3 studies ( 76 78 )], Canada [3 studies ( 79 – 81 )], Netherlands [3 studies ( 82 84 )], Spain [3 studies ( 85 87 )], Australia [2 studies ( 88 , 89 )], Singapore [2 studies ( 90 , 91 )], Korea [2 studies ( 92 , 93 )], Finland [1 study ( 94 )], Italy [1 study ( 95 )], Ireland [1 study ( 96 )], Colombia [1 study ( 97 )], Pakistan [1 study ( 98 )], Thailand [1 study ( 99 )], Iran [1 study ( 100 )], Poland [1 study ( 101 )], Mexico [1 study ( 102 )], Norway [1 study ( 103 )], Saudi Arabia [1 study ( 104 )], and Switzerland [1 study ( 105 )]. The distribution of included studies among different continents was shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Tsai et al (2018) indicated that a well-designed skill simulation system could simulate authentic operation situations, allowing learners to clearly learn important concepts through self-control, interaction, simulation, and observation, thereby effectively enhancing the LO. Han et al (2021) conducted the inspection and research of nervous system teaching tools based on VR. The research results implied that VR technology could effectively improve students’ learning satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%